DISCOURSE MARKERS IN NARRATIVE TEXTS IN ENGLISH TEXTBOOK OF SENIOR HIGH SCHOOL STUDENTS - Saida Azmi Damanik; Siti Aisah Ginting (Universitas Negeri Medan, 2022)
The objectives of the study were to find out the types and function of discoursemarkers that used in the narrative texts. The study was conducted by applying adescriptive qualitative research. The data of the research were 10 narrative textstaken from an English textbook for grade XI senior high school students entitledEnglish in Use. The data were analyzed by using Fraser Taxonomy (1999). It wasfound 5 types: Contrastive Markers, Elaborative Markers, Inferential Markers,Reason Markers and Sequential. However, There are 3 types of discourse markerswhich were not found in the narrative texts, they are Conclusive, Exemplifier andTopic Relating markers. Furthermore, the data were also analyzed by usingBrinton (1996). It was found 2 functions: Textual Function and InterpersonalFunction. The textual function was the most dominant function found in thenarrative texts.